Pengaruh Metode Bercerita Terhadap Perkembangan Kognitif Anak Usia Dini - Akwila Kase; Delila Plaikol; Grace Selan; Ordia Nubatonis; Putri Tanesib; Yulinda Bani; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
Cognitive development is an important aspect that affects the thinking ability of young children. The purpose of this study is to find out the effect of storytelling method on the cognitive development of young children. The method used in this research is quantitative. The sampling technique used is total sampling, meaning the children 5-6 years at PAUD Alfa Omega II Manutapen were included. The number of respondents in this study was 36 young children at PAUD Alfa Omega II Manutapen. The data collection technique used questionnaires and observation sheets with instruments in the form of a storytelling method scale and a young children's cognitive development scale. The storytelling method scale was developed based on indicators of storytelling method application in early childhood learning. The cognitive development scale was developed based on indicators of early childhood cognitive development. The data analysis technique used is simple linear regression. The findings of this study show that the storytelling method has a positive and significant effect on the cognitive development of young children, amounting to 28,3%. This means that the better the application of the storytelling method, the higher the cognitive development of young children at PAUD Alfa Omega II Manutapen. It is hoped that teachers can apply the storytelling method in a creative, consistent, and enjoyable way so that it can stimulate children's thinking ability, memory, concentration, and problem-solving skills.